2019
DOI: 10.1080/14789949.2019.1638959
|View full text |Cite
|
Sign up to set email alerts
|

An exploration of the support provided by prison staff, education, health and social care professionals, and prisoners for prisoners with dementia

Abstract: The prison population is aging, and older prisoners are at a higher risk of developing dementia than their community dwelling counterparts. Currently there is limited information on the support provided for prisoners with dementia. The aim of this study was to gain an understanding of the lived experience of prison staff, education, health and social care professionals and prisoners with a social care role who supported men with dementia in prison. The study was completed in a Category C male prison in England… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 27 publications
(32 reference statements)
1
12
0
Order By: Relevance
“…For example, initially, the code "We Balance Safety and Security" to "We Balance Safety & Security with Empathy." Some other works have supported the idea of refining preliminary results [6,16,25].…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…For example, initially, the code "We Balance Safety and Security" to "We Balance Safety & Security with Empathy." Some other works have supported the idea of refining preliminary results [6,16,25].…”
Section: Discussionmentioning
confidence: 91%
“…In these progressive prisons, prison staff appear to be the arbiters who interpret and apply family-centric practices and protocols [12][13][14][15]. However, there are significant implementation differences in how prison staff carry out and enact their roles within UK penal institutions [16]. The purpose of this qualitative multiple case study was to understand how prison staff interpreted their roles during family visits and to determine why this evolution towards family-focus visiting took place.…”
Section: United Kingdom Family-oriented Prisonsmentioning
confidence: 99%
“…With the image-text communication-based healthcare education combined with shifting of attention, the intervention plan meeting the interest of child patients was formulated to shift their attention and fear about disease, pain, and surgery, reduce their attention to pain, so that they could relax muscles and slow down the breathing frequency, which alleviated their pain sensation to some extent, and combined with the education to the child patients and their parents in the perioperative period, enhanced their confidence in fighting the disease and pain [ 17 19 ]. In addition, rich and interesting content, such as pictures, audios, and videos, could promote the interest of the child patients and directly improve the adverse emotions, and the child patients' trust in the medical staff could be enhanced with the positive encouragement of medical staff and their family members and effective communication.…”
Section: Discussionmentioning
confidence: 99%
“…14 There is recognition that health care staff in the prison need training to enable them to assess and identify early signs of dementia, and there is recognition that staff have difficulty in distinguishing between mental health, dementia, and drug-induced symptoms, thus supporting the need to provide specific training. 49 One strategy to improve staff knowledge about caring for people with dementia was to develop dementia champions. 4,38 This strategy found that an expert in dementia within the correctional health team could guide staff training, as well as development of practice guidelines, and become a resource for less experienced staff.…”
Section: Discussionmentioning
confidence: 99%
“…Brooke and Jackson 49 identified the need to develop evidence-based guidelines and policies to strengthen staff training in cognitive screening and monitoring to care for prisoners with dementia. Furthermore, experts in the field, supported by the findings of qualitative studies, have called for policies, procedures, and protocols to be developed related to training for staff caring for prisoners with dementia 18,49 . The development of policies incorporating dementia training for staff can provide frameworks to support decision-making related to dementia-centered care.…”
Section: Discussionmentioning
confidence: 99%